The ground-penetrating radar (GPR) method in the characterization of the Monastery of Batalha - Barraca, Nuno; Matias, Manuel; Almeida, Fernando (Conservar Património, 2019)
The characterization of the Monastery of Batalha included the use of the geophysical method of ground-penetrating radar (GPR), a non-destructive and indirect method that provides highresolution 2D/3D images of the structures to investigate. Owing to the nature and aims of the survey, appropriate measurement grids, acquisition parameters and adapted data processing techniques were used. The GPR survey provided important information about the Monastery foundations, construction and conservation. GPR high-resolution images allowed to locate recent and ancient infrastructures, columns foundations and structures of historical-archaeological interest. The characterization of the Monastery walls was also carried out using GPR on the surface of walls of the Cloister of D. João I and of the Church. These results contribute for the proposal of an inner structure model of the walls. GPR proved to be an efficient and expeditious method that allowed obtaining information to be used in the preservation, recovery and rehabilitation of the Monument. Received: 2018-11-9 Revised: 2019-1-8 Accepted: 2019-1-29 Online: 2019-3-18 Publication: 2019-11-6